SELF-REGULATED CHILDREN’S GROUP AS A STAGE OF CHILD’S SOCIALIZATION - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article is devoted to the study of the activities of one of the institutions of children’s socialization – a self-regulated children's group. The self-regulated children's group is a voluntary gathering of children living in the same neighborhood. Until recently, such a group played a significant role in nurturing in a person such qualities that are required in society: the ability to negotiate with others, the ability to defend one's opinion in permitted manner, the ability to act in accordance with the rules accepted in society, the ability to work for the benefit of others, etc.The aim of the study was to determine the presence of the group as a socialization institution, the features of the group's emergence in a historical context, the characteristics of Latvian children's groups, their structure, territory, dwellings, activities.Child’s participation in a self-regulated children's group is a necessary stage of socialization in a traditional society.The study, based on which one can explain the existence of a self-regulated children's group, was made by M.V. Osorina. She examined the concept of the world in the consciousness of an individual and the formation of this concept at various stages of the child's development. The formation of the image of the world occurs due to the mastery of space: his own body, family home, the place where the child lives. The child's territorial space increases as he grows up. He inhabits each of these places, and goes from social-daily to deeply-significant knowledge. When the child's territory expands and goes beyond the boundaries of his yard, he lives in it with other children. In author’s opinion, when they gather in groups, children begin visiting places that until then were forbidden. According to M.V. Osorina, this territory includes the "boundaries", "ways" along which every child loves to walk, and a "place" – the locus of space where a person satisfies any needs and experiences certain feelings. Such places are places for games, "scary" places, places of existential-philosophical and religious experiences, "interesting" places, places of meetings, places of solitude. A unique material was collected by the author about the "headquarters" that the children built in their territory.The group facilitates the formation of a group identity through the development of the idea of "Us" in joint walks, games, pranks, etc. Belonging to the group is strengthened by the use of secret "languages", incomprehensible to the uninitiated.An old study of R. Hurt (1978) reveals the features of territorial behavior of children in a small American town. He found that from 7 to 14 years of age, the boundaries of space that children live in expand rapidly. According to the author, this is due to the entry of children into school. Boys always take up a space 1,5-2 times larger than girls. At the age of 14, children no longer tend to explore new spaces, but live within known limits.Looking ahead, we would like to note that according to our data, at this age most children are already leaving the self-organized children's group. Consequently, the territory expands as long as the group needs it, and the active research behavior is more in the interest of the group than of each individual child.